Histone Deacetylase SIRT1 Mediates C5b-9-Induced Cell Cycle in Oligodendrocytes - Tatomir, Alexandru; Rao, Gautam; Boodhoo, Dallas; Vlaicu, Sonia I.; Beltrand, Austin; Anselmo, Freidrich; Rus, Violeta; Rus, Horea (Frontiers in Immunology, 2020)
Sublytic levels of C5b-9 increase the survival of oligodendrocytes (OLGs) and induce the cell cycle. We have previously observed that SIRT1 co-localizes with surviving OLGs in multiple sclerosis (MS) plaques, but it is not yet known whether SIRT1 is involved in OLGs survival after exposure to sublytic C5b-9. We have now investigated the role of SIRT1 in OLGs differentiation and the effect of sublytic levels of C5b-9 on SIRT1 and phosphorylated-SIRT1 (Ser27) expression. We also examined the downstream effects of SIRT1 by measuring histone H3 lysine 9 trimethylation (H3K9me3) and the expression of cyclin D1 as a marker of cell cycle activation. OLG progenitor cells (OPCs) purified from the brain of rat pups were differentiated in vitro and treated with sublytic C5b-9 or C5b6. To investigate the signaling pathway activated by C5b-9 and required for SIRT1 expression, we pretreated OLGs with a c-jun antisense oligonucleotide, a phosphoinositide 3-kinase (PI3K) inhibitor (LY294002), and a protein kinase C (PKC) inhibitor (H7). Our data show a significant reduction in phospho-SIRT1 and SIRT1 expression during OPCs differentiation, associated with a decrease in H3K9me3 and a peak of cyclin D1 expression in the first 24 hours. Stimulation of OLGs with sublytic C5b-9 resulted in an increase in the expression of SIRT1 and phospho-SIRT1, H3K9me3, cyclin D1 and decreased expression of myelin-specific genes. C5b-9-stimulated SIRT1 expression was significantly reduced after pretreatment with c-jun antisense oligonucleotide, H7 or LY294002. Inhibition of SIRT1 with sirtinol also abolished C5b-9-induced DNA synthesis. Taken together, these data show that induction of SIRT1 expression by C5b-9 is required for cell cycle activation and is mediated through multiple signaling pathways.